Moderate exercise reveals the influence of ACTN3 R577X and ACE I/D polymorphisms on physical performance in non-athlete active subjects - Alvero-Cruz, José Ramón; Alarcón-Martín, Emilio; García-Romero, Jerónimo; Ruiz-Galdón, Maximiliano; Carrillo-de-Albornoz, Margarita; Polvillo, Rocío; González, Irene; Reyes-Engel, Armando; Royo-Sánchez-Palencia, José Luis (Elsevier, 2023)
Genome variations contribute to the vast majority of interindividual differences and may decisively influence sports capability. This study was conceived as a means of finding out when exactly polymorphisms start being physically discriminative. The polymorphisms we studied were two of the best characterized ones: ACE I/D and ACTN3 R577X. These germline variants were determined in a cohort of 200 healthy volunteers from the university environment who underwent a series of physical evaluations that included a Cooper test, a 20-meter sprint test and a vertical jump test. Initially, no statistical association was found because the genetic effect was masked by those subjects with sedentary lifestyles. But when only physically active volunteers were considered, the ACE and ACTN3 genotypes were found to have an impact on heart rate after the Cooper test (p-value = 0.033 and 0.032 respectively) and ACTN3 was found to correlate with the total distance covered in the same test (p-value = 0.051). This can therefore be considered a paradigmatic example in which the environment might hide the genetic effect, with genotypic differences arising only upon training. © 2022
Keywords: Polimorfismo genético; Condición física - Evaluación; Ejercicio físico; Actinin; Exercise; Genotype; Humans; Peptidyl-Dipeptidase A; Physical Functional Performance; Polymorphism, Genetic; Actinin; Exercise; Genotype; Humans; Peptidyl-Dipeptidase A; Physical Functional Performance; Polymorphism, Genetic